CHE469: Materials and energy balance / College of Engineering - UiTM, College of Engineering (2023)
This course is presents an introduction to mass and energy balances. The students are exposed to advanced material and energy balances concepts to solve problems of unit operation in chemical processing of reactive and unreactive system.